1998
DOI: 10.1007/s004390050764
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CCR5-delta 32 gene deletion across the Russian part of Eurasia

Abstract: 32-bp inactivating deletion in the beta-chemokine receptor 5 (CCR5) gene, common in Nothern European populations, is associated with reduced HIV-1 transmission risk and delayed disease progression. We have studied the deletion distribution in many populations in Eurasia by polymerase chain reaction analysis of 531 DNA samples representing West and East Siberian, Central Asian, and Far Eastern parts of Russia. An unusually high frequency (11.1%) of the deleted variant in natives of West Siberia, of Finno-Ugrian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
1
10
0
7
Order By: Relevance
“…The CCR5D32 allele frequency found in this study was similar to the frequencies previously reported for Russia. It is interesting to note that the closest figures were found previously in Moscow (0.095, x 2 5 0.31, p 5 0.57) (Kazennova et al, 1998), whereas the frequencies for other regions of Russia were higher (range, 0.11-0.13) (Aseev et al, 1997;Slominskii et al, 1997;Voevodin et al, 1998;Yudin et al, 1998). This could be due to higher proportion of FinnoUgrian population, characterized by high frequency of this allele (Pastinen et al, 1998), in the cohorts from those studies.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The CCR5D32 allele frequency found in this study was similar to the frequencies previously reported for Russia. It is interesting to note that the closest figures were found previously in Moscow (0.095, x 2 5 0.31, p 5 0.57) (Kazennova et al, 1998), whereas the frequencies for other regions of Russia were higher (range, 0.11-0.13) (Aseev et al, 1997;Slominskii et al, 1997;Voevodin et al, 1998;Yudin et al, 1998). This could be due to higher proportion of FinnoUgrian population, characterized by high frequency of this allele (Pastinen et al, 1998), in the cohorts from those studies.…”
Section: Resultssupporting
confidence: 69%
“…At the same time, limited information concerning only the CCR5D32 distribution in several regions of the Russian Federation is currently available (Aseev et al, 1997;Slominskii et al, 1997;Kazennova et al, 1998;Voevodin et al, 1998;Yudin et al, 1998). The aim of this study was (1) to determine the distribution of CCR5D32, CCR5-59029A/G, CCR2-64I, and SDF1-39A alleles among a representative sample of the Moscow population and (2) to estimate the co-occurrence or genotypic independence of those alleles.…”
Section: Introductionmentioning
confidence: 97%
“…Recently the protection from AIDS was found for a 32-bp depletion in the chemokine receptor gene CCR5 [87,88]. The distribution of the mutation varies in human populations from 11-15% among Caucasian people in Northern Europe to 0 % among Inuites in Canada [89,90]. Contrary to androgen-suppressed acquired (adaptive) immune system [27], innate resistance is formed by presumably androgenindependent mechanisms.…”
Section: Showiness Dominance and Immunocompetencementioning
confidence: 99%
“…По данным литературы известно, что нарушение функции рецептора CCR5 в результате делеции 32 п.н. может выступать патоге-нетически значимым фактором в развитии заболеваний [13]. Сведения об ассоциации CCR5del32 с риском заболевания БА немногочисленны и противоречивы [6,9,11].…”
Section: оригинальные исследованияunclassified